Geostatistical based soil fertility mapping of Horticultural Research Station, Rajikot, Jumla, Nepal - Khadka, Dinesh; Lamichhane, Sushil; Giri, Raj K.; Chalise, Basant; Amgain, Rita; Joshi, Sushila (Journal of Agriculture and Natural Resources, 2020)
Geostatistical soil mapping is important for determining spatial distribution of soil parameters. This study was conducted to assess soil spatial distribution of the Horticultural Research Station, Rajikot, Jumla, Nepal. The total 27 samples were collected randomly at a depth of 0-20 cm by using soil sampling auger. A GPS device was used for determination of geographical position of soil sampling points. The collected samples were analyzed following standard analytical methods in the laboratory of National Soil Science Research Centre, Khumaltar. The Arc-GIS 10.1 software was used for the mapping spatial distribution of various soil parameters. The observed data revealed the structure was sub-angular blocky and granular, whereas colour were dark brown to dark grayish brown and dark yellowish brown. The sand, silt and clay content were ranged 24.40-72.10%, 19.40-63.10% and 6.20-14.50%, respectively and categorized loam, sandy loam and silt loam in texture. The soil pH was slightly acidic to moderately alkaline (5.01-8.06), and very low available sulphur (0.59-2.41 mg/kg) and very low to low available boron (0.04-0.87 mg/kg).  Moreover, very low to medium available manganese (2.18-13.46 mg/kg), very low to very high available iron (4.50-138.58 mg/kg), and low to medium available magnesium (7.20-177.60.53 mg/kg) and zinc (0.26-1.66 mg/kg). Similarly, medium total nitrogen (0.09-0.22%), medium to high organic matter (1.71-6.26%) and available calcium (1200-3144 mg/kg), medium to very high available phosphorus (3.71-82.4 mg/kg) and potassium (59.37-173.05 mg/kg). Correspondingly, high to very high available copper (0.78-4.20 mg/kg). The determined soil test data can be used for sustainable soil management as well as developing future research strategy in the farm.